Reference Values for Hematology, Plasma Biochemistry, Bone Marrow Cytology and Bone Histology of NOD.Cg-Prkdc(scid) Il2rg(tm1Wjl)/SzJ Immunodeficient Mice - Layssol-Lamour, Catherine J (J Am Assoc Lab Anim Sci, 2021)
Highly immunodeficient NSG mice (NOD.Cg-Prkdc(scid) Il2rg(tm1Wjl)/SzJ) are commonly used as a models in preclinical studies for patient-derived engraftment. However, despite the frequency of their use, reference values for their clinical pathology markers have not been determined. In accordance with the American Society of Veterinary Clinical Pathology (ASVCP) recommendations, we established de novo reference values for hematologic and biochemical variables and evaluated bone marrow cytology and histology in forty 9-wk-old male and female NSG mice. Hematologic analyses were performed using 2 separate analyzers (IDEXX ProCyte Dx, Sysmex XT-2000iV) and biochemical values were measured using a Scil VetScan2. The primary hematologic characteristic seen in NSG mice was a very low white blood cell (WBC) count (below 1.6 10(9)/L). Lymphocyte and monocyte counts were respectively over- and under-estimated by the analyzers, as compared with manual counts, likely due to misidentification of the very low concentrations of these cell types by the analyzers. This analytical bias highlights the need for confirmatory microscopic observation of blood smears from these mice for WBC differential identification. Results for all other hematology and biochemistry variables were similar to those previously reported in inbred mice, except for MPV and an unexpectedly high glucose concentration (11.5 to 19.0 mmol/L), potentially due to the nonfasting status of the animals. The differential bone marrow cell count and Myeloid:Erythroid ratio (median 1.76) were also established. Megakaryocyte and adipocyte count differed significantly between the femoral diaphysis and metaphysis and between genders. These results provide a reliable resource of baseline data for hematologic variables for researchers monitoring graft rejection studies in NSG mice.